Antibacterial Evaluation of Nerium Oleander Extract Enhanced by Titanium Oxide Nanoparticles - Makia, Raghada S. A (Al-Nahrain Journal of Science, 2018)
The antimicrobial activities of ethanolic extract of the Nerium oleander have been screened by anti-bacterial action against Staphylococcus aureus, Klebsiella pneumonie and Escherichia coli utilizing the disc diffusion test. An endeavor was additionally made to enhanced the antimicrobial activity of the ethanolic extract of Nerium oleander by blending of TiO2 nanoparticles with Nerium oleander extract. In view of the general results, the ethanolic extract of Nerium oleander enhanced by TiO2 Nps demonstrated the most activities against a wide range of tested bacteria, yet the ethanolic extract alone was observed to be dynamic against the S. aureus and E. coli, while a powerless antibacterial activity was observed against the ethanolic extract demonstrate a K. pneumonie. Inhibition efficiency increased with increasing concentration of the ethanolic extract of and also with enhanced by TiO2 Nps. The inhibition zone at the concentration 300 mg/mL in presence and absence of TiO2 NPs were 21 mm and 24 mm against Staphylococcus aureus and against Klebsiella pneumonie were 12 mm and 25 mm, finally for Escherichia coli were 23 mm and 29 mm respectively.